The development of motor abilities of young athletes and gymnasts in the initial preparation phase - Dobrijevic, S.; Cosic, M.; Kocic Pajic, S.; Grujic, S.; Moskovljevic, L. (Facta Universitatis: Series Physical Education and Sport, 2020)
The aim of this study is to determine the effect of sports gymnastics and athletics training on the development of athletes` motor abilities in the initial preparation phase. The study was conducted on a sample of 81 girls and boys of about 9 years of age, who train athletics (N=34) and gymnastics (N=47). A total of 9 variables were observed, three to assess anthropometric characteristics (body height, body mass and the body mass index) and 6 to assess the participants` motor abilities (explosive leg power, repetitive power, agility, power endurance, flexibility, cardiorespiratory endurance). The one-sample t-test was used to compare the results with mean values of the general population of the same age, whereas a univariate ANOVA was used to compare the results between the athletes and the gymnasts of different genders. The results show that the level of motor development in girls is significantly higher than in the general population, while in boys, significant progress was not registered in power endurance and cardiorespiratory endurance, regardless of the sport they are engaged in. Regardless of gender, gymnasts have better flexibility compared to athletes, while athletes have significantly higher explosive power and agility.